System mierników dla banku informacji o gospodarce zlewni górnej Noteci - Domański, Ryszard (Wydział Prawa i Administracji UAM, 1980)
It is indicated by experience of countries and regions, which reached particularly high economic effects owing to irrigation, that taking that investment as a starting point a whole set of stimuli which impel agricultural production and re-shape agriculture and food-stuff economy has to be set in motion. Changes influenced by these transformations occur in the whole regional economy what calls for a comprehensive approach to development of regions based on water economy. System of standards can not be restricted to characteristics of relation: irrigations — growth in agriculture output — development of foodstuff industry. Other related factors of growth in agriculture output and foodstuff industry and a whole chain of direct and indirect effects must be characterized as well. After discussion of factors that shape the system and of it's features and forms, a topical structure of system of standards for the agricultural and foodstuff complex has been outlined in the second part of the elaboration.
System of Standards for the Information Bank of the Upper Noteć Basin Economy